PEMANFAATAN APLIKASI PERPUSTAKAAN DIGITAL iJATENG MELALUI SMARTPHONE - Endang Fatmawati (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This research as a preliminary study to know the utilization of iJateng application through android. The purpose is to explain the accessibility and usability of digital library in improving community knowledge, and to identify the factors that become obstacles in the utilization of Jateng. The research method used qualitative. Data were obtained using interview technique and document search. Utilization is described using accessibility and usability parameters. The result of this research concludes that accessibility to openness aspect has not been fully socialized to society. Furthermore, for usability on the aspect of learnability, it is still necessary assistance from the library manager to reduce the obstacles that arise when people use iJateng applications through smartphones. Factors that become obstacles in the utilization of digital library iJateng, such as: Internet network problems, incomplete digital collections, eyestrain, lack of socialization, and lack of readers to solve problems that arise when accessing information through the application iJateng.